Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae) - Huber, Bernhard A. (Zootaxa, 2020)
Hoplopholcus Kulczyński, 1908 is a genus of relatively large pholcid spiders, ranging from eastern Central Europe to Crete, the Levant, and Georgia. Species in this genus are often difficult to distinguish from each other, and the reexamination of previously published material revealed many misidentifications. The present study provides redescriptions of the ten previously described species and descriptions of six new species, all based on males and females: Hoplopholcus suluin sp. n., H. konya sp. n., H. atik sp. n., and H. bursa sp. n. from Turkey, H. gazipasa sp. n. from Turkey and Greece, and H. dim sp. n. from Turkey and Cyprus. The main conclusion is that several species need further investigation, based on focused sampling and ideally including molecular data. Some species seem to include morphologically distinct epigean and hypogean populations; others may eventually need to be split into two or more species. Further undescribed species are most likely to occur in Turkey.